The Role of adaptive MSCs as an Attempt Regeneration of Spermatogenesis Process Using by Hypoxia Precondition In Vitro - erma safitri (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
The aim of this research was to obtain to get adaptive MSCs by an treatment in hypoxia precondition in viro culture. Ini this research, hypoxia precondition was to be given 3% O2 concentration and compared to those of normoxia culture in O2 > 20%. Results showed that under 3% O2 concentration, CD105+ and CD45- by flowcytometri, immunocytokimia and immunofluorescence didn’t experience of change (undifferentiated). Meanwhile under > 20% O2 concentration, cells have experienced of change (not undifferentiated again), that was indicated with CD105+ become decrease and CD45- increase by flowcytometri, immunocytokimia and immunofluorescence. Conclusion, in this research showed that hypoxia precondition with 3% O2 concentration very support MSCs to constantly adaptive before transplantated for disturbance of spermatogenesis process, because did’nt experience become progenitor cells was not expectation (still undifferentiated).